The land of stories the enchantress returns - Colfer, Chris (The land of stories, 2014)
Alex and Conner Bailey have not been back to the magical Land of Stories since their adventures in The Wishing Spell ended. But one night, they learn the famed Enchantress has kidnapped their mother! Against the will of their grandmother, the twins must find their own way into the Land of Stories to rescue their mother and save the fairy tale world from the greatest threat it's ever faced.